2013
DOI: 10.1590/s1516-35982013000100010
|View full text |Cite
|
Sign up to set email alerts
|

Copper and selenium supplementation in the diet of Brangus steers on the nutritional characteristics of meat

Abstract: -Twenty-eight Brangus cattle were used to determine the effect of copper and selenium supplementation on the carcass characteristics, fatty acid composition of the longissimus dorsi muscle and on the copper and selenium concentrations in the liver. The treatments were: no supplementation of copper or selenium; 2 mg Se/kg DM as sodium selenite; 40 mg Cu/kg DM as copper sulfate; and 2 mg Se/kg DM as sodium selenite and 40 mg Cu/kg DM as copper sulfate. The fat thickness, rib eye area and fatty acid composition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…That water is mainly held by capillary forces resulting from the arrangement of the thick and thin filaments within the myofibril (Huff-Lonergan and Lonergan 2005). The present results are in agreement with those reported by Netto et al (2013), who did not demonstrate significant effects of Se supplementation on meat cooking loss. The cooking losses in this experiment were close to the values reported by Cozzi et al (2011) at 34.6% in Charolais cattle supplemented with Se.…”
Section: (supporting
confidence: 94%
See 2 more Smart Citations
“…That water is mainly held by capillary forces resulting from the arrangement of the thick and thin filaments within the myofibril (Huff-Lonergan and Lonergan 2005). The present results are in agreement with those reported by Netto et al (2013), who did not demonstrate significant effects of Se supplementation on meat cooking loss. The cooking losses in this experiment were close to the values reported by Cozzi et al (2011) at 34.6% in Charolais cattle supplemented with Se.…”
Section: (supporting
confidence: 94%
“…Cozzi et al (2011) previously reported no effects of Se supplementation for the slaughter performance of Charolais bulls managed through different feeding strategies. Netto et al (2013) observed no significant differences in carcass yield of steers from the Brangus breed receiving a diet supplemented with Se at 2 mg kg…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Selenium enrichment of the diet of young fattening bulls and steers had no significant effect on weight at slaughter and carcass yield. These effects were observed in the studies of Lawler et al [78] with organic selenium (selenized yeast), Netto et al [79] with the mineral selenium and Mehdi et al [68] with the cereals produced from the fertilizer selenium enriched soil.…”
Section: The Effects Of Selenium Supplementationmentioning
confidence: 80%
“…Part of the absorbed organic selenium is incorporated directly into the muscle proteins, while the inorganic selenium is mainly used for the synthesis of selenoproteins [102,103]. Inorganic selenium supplementation provides no significant difference in the selenium concentration in the muscles [78,79,85]. During a selenite supplementation, most of the selenium is incorporated in selenoproteins.…”
Section: The Effects Of Selenium Supplementationmentioning
confidence: 99%